Atheroma Progression in Hyporesponders to Statin Therapy. Issue 4 (April 2015) - Kataoka, Yu; St. John, Julie; Wolski, Kathy; Uno, Kiyoko; Puri, Rishi; Tuzcu, E. Murat; Nissen, Steven E.; Nicholls, Stephen J.
<x xml:space="preserve">Abstract</x> Objective— Lowering low-density lipoprotein cholesterol (LDL-C) with statins has been demonstrated to slow plaque progression. This antiatherosclerotic effect in patients with minimal LDL-C lowering has not been investigated. Approach and Results— Six hundred forty-seven patients with angiographic coronary artery disease who were commenced on statin therapy underwent serial imaging with intravascular ultrasound. Responders were defined as a percentage reduction in LDL-C of <15%. Disease progression was compared in responders (n=517) and hyporesponders (n=130) to statin therapy. Twenty percentage of patients demonstrated minimal changes in LDL-C, despite commencement of statin therapy. Statin hyporesponders were younger (55 versus 57 years; P=0.01), more likely to be male (79% versus 66%; P=0.005), and obese (body mass index, 31.5±6.1 versus 30.3±5.9 kg/m2; P=0.04) and less likely to have a history of dyslipidemia (50% versus 66%; P<0.001). Baseline levels of systolic blood pressure (127±15 versus 132±17 mm Hg; P=0.01) and LDL-C (2.5±0.6 versus 3.4±0.8 mmol/L; P<0.001) were lower in statin hyporesponders. Baseline percent atheroma volume was similar between statin hyporesponders and responders (36.9±9.8% versus 38.3±9.2%; P=0.13). On serial evaluation, greater progression of percent atheroma volume (1.19±0.48% versus 0.09±0.43%; P=0.003) was observed in statin hyporesponders. After adjusting for baseline clinical characteristics and measures of plaque burden, statin hyporesponders still exhibited greater atheroma progression (+0.83±0.58% versus −0.21±0.52%; P=0.006). Conclusions— A substantial proportion of patients with coronary artery disease fail to achieve effective reductions in LDL-C, despite prescription of statin therapy. Greater progression of atherosclerosis is observed in these patients. Our current study underscores monitoring LDL-C level after the commencement of statin to ensure adequate response to statin therapy.